Osteochondritis Dissecans - Helmi Ismunandar (CV. Jasa Sukses Abadi, 2020)
Osteochodritis dissecans (OCD) is a focal change in the subcondral bone. This alteration results in either partial or complete osteochondral fragmentation. OCD usually suffered by athletes (children, adolescents, or adults). Osteochondritis dissecans is source of pain and knee dysfunction during adolescent growth. It need to detected early to avoid secondary osteoarthritis. It most commonly occurs in the knee (75%), elbows (5%), and ankles (4%). Total incidence of OCD in the distal femur is 6,09 per 100.000 people per year. Male’s incidence (8,82-10 per 100.000) is higher than women’s (3,32- 4,04 per 100.000). Juvenile type knee OCD usually occurs at age 11,3-13,4 years. The average age on adult OCD is 17- 36 years. The pathogenesis of OCD is still not fully understood. Impact injuries can cause edema or bleeding in the subarticular bone. Local ischemic arises due to capillaries squeezing or thrombus formation. In certain circumstances, osteochondral fractures or fragmentation can occur. OCD can be treated both nonoperatively and operatively.